Pea Fusarium wilt races in western Algeria - Aoumria Merzoug; Lakhdar Belabid; Mokhtar Youcef-Benkada; Fouzia Benfreha; Bassam Bayaa (Plant Protection Science, 2014)
The fungus Fusarium oxysporum f.sp. pisi (FOP), the pea wilt pathogen, causes appreciable yield losses under favourable environmental conditions in Algeria. Studies on the pathogen variability and distribution of races are essential to identify effective sources of resistance to this disease. In this study, a survey was conducted during the period 2007-2011 in four different agro-climatic zones. Pathogenic variability in 52 isolates of FOP, collected from different pea-growing areas of western Algeria, were evaluated using 7 genotypes as differential hosts. Results indicated that the disease was prevalent in all fields prospected and isolates obtained were assigned to Races 1, 2, 5 or 6 by their pathogenicity. It was found out that Races 1 and 2 were more common in all areas with 61.5 and 19.2%, respectively. This study is the first report of pea Fusarium wilt races distribution in Algeria.